Mengoptimalkan Peran Lembaga Perfilman Indonesia: Analisis Aspek Hak Cipta terhadap Praktik Siaran Video Ilegal - Relys Sandi Ariani; Luna Dezeana Ticoalu; Herlin Sri Wahyuni (University of Jember, Indonesia, 2021)
The film is part of the intellectual property rights attached to the creator. Nowadays, it is commonly agreed that violation of intellectual property rights portrays in film piracy for personal gain is inevitable, with illegal streaming services. This study aimed to examine film protection, conduct a study of film institutions, and find concepts to protect films in Indonesia. The study used a juridical method with the statute and conceptual approaches. In so doing, it used secondary data processed using library research techniques. The study showed that illegal movie streaming rampant in Indonesia practiced illegal streaming movies. It violated the intellectual property rights inherent in the creator, resulting in enormous losses for the creators. There are further problems in the laws and regulations, and the government must accommodate preventive actions. This study suggested three components: correctional, supervision, and copyright protection against illegal movie streaming in Indonesia; and these components were to maximize the role of stakeholders. KEYWORDS: Illegal Streaming Movies, Indonesian Film Institute, Intellectual Property Rights and Copyrights